Ontogenesis of the asymmetric parapineal organ in the zebrafish epithalamus - Palma, Karina; Signore, Iskra A.; Meynard, Margarita M.; Ibarra, Jazmin; Armijo-Weingart, Lorena; Cayuleo, Marcos; Härtel, Steffen; Concha, Miguel L. (Frontiers in Cell and Developmental Biology, 2022)
The parapineal organ is a midline-derived epithalamic structure that in zebrafish adopts a left-sided position at embryonic stages to promote the development of left-right asymmetries in the habenular nuclei. Despite extensive knowledge about its embryonic and larval development, it is still unknown whether the parapineal organ and its profuse larval connectivity with the left habenula are present in the adult brain or whether, as assumed from historical conceptions, this organ degenerates during ontogeny. This paper addresses this question by performing an ontogenetic analysis using an integrative morphological, ultrastructural and neurochemical approach. We find that the parapineal organ is lost as a morphological entity during ontogeny, while parapineal cells are incorporated into the posterior wall of the adult left dorsal habenular nucleus as small clusters or as single cells. Despite this integration, parapineal cells retain their structural, neurochemical and connective features, establishing a reciprocal synaptic connection with the more dorsal habenular neuropil. Furthermore, we describe the ultrastructure of parapineal cells using transmission electron microscopy and report immunoreactivity in parapineal cells with antibodies against substance P, tachykinin, serotonin and the photoreceptor markers arrestin3a and rod opsin. Our findings suggest that parapineal cells form an integral part of a neural circuit associated with the left habenula, possibly acting as local modulators of the circuit. We argue that the incorporation of parapineal cells into the habenula may be part of an evolutionarily relevant developmental mechanism underlying the presence/absence of the parapineal organ in teleosts, and perhaps in a broader sense in vertebrates.